Wage ceilings and floors: the gender gap in Ukraine's transition - Ina Ganguli; Katherine Terrell (Institute for the Study of Labor (IZA), 2005)
This paper uses new micro data from the Ukrainian Longitudinal Monitoring Survey (ULMS) to examine the gender gaps across the distribution of wages in Ukraine during communism (1986), the start of transition (1991), and after Ukraine started to be considered a market economy (2003). We find that the gender pay gap is higher in the top half of the distribution than at the bottom half and that this 'glass ceiling' is persistent across the three points in time, while the wage floor rose for women in 2003. Closer inspection of two sectors the private and the public reveals the striking finding that the glass ceiling is lower in the public than in the private sector but the floor is the same. We use the Machado and Mata (2004) method to create counterfactuals that advance our knowledge of which factors are driving these differences; we find that the differences in men's and women's rewards (ßs) rather than differences in their productive characteristics (Xs) explain most of the wage gap throughout the distribution. The different ceilings in the public and private sectors are largely due to differences in men's and women's productive characteristics, which favor men in the public and women in the private sector. The fall in the gender gap in the lower part of the distribution from 1986 to 2003 is explained partially by the improvement in women's productive characteristics and partially by the worsening in men's rewards in the bottom half of the distribution over time. However, probably the most important reason for the reduction in the gap at the bottom of the distribution over time is that the value of the minimum wage was set relatively high in 2003 and it raised the wage floor for more women than men.
Keywords: C14; I2; J16; 330; gender gap; quantile regression; glass ceilings; glass floors; transition; Ukraine